Association of rs763780 Polymorphism of IL 17F Gene with Risk of Rheumatoid Arthritis in Uzbekistan - A. A. Eshmurzayeva; А. А. Qurbonqulov (Scholars Digest Publishing, 2023)
As a result of our studies, we found that the G allele and the heterozygous A/G genotype of the IL 17F gene (rs763780) are significantly higher among patients with rheumatoid arthritis compared to the control group. In particular, the most significant differences were found in patients with the articular visceral form of the disease, in whom the G allele exceeded the proportion of the carrier in the control statistically significantly by 2.58 times (χ2=4.512; P=0.037; OR=2.58; 95%CI:1.076-6.188), and on the part of the heterozygous genotype A/G, there was a clear tendency to increase its frequency more than twice (χ2=2.011; P=0.165; OR=2.068; 95% CI: 0758-5.645), which in turn indicates the possible participation of the studied polymorphism in pathogenesis of RA.
Keywords: rheumatoid arthritis, rs763780 polymorphism of IL 17F gene, allele carrier, genotype, risk of development.